THE ENVIRONMENT BUILT AND THE CITIES IN JANE JACOBS'´S WORK - de Oliveira, Edilson Luis (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.826, 2020)
This article aims to highlight the theoretical, analytical and ethical perspective on contemporary cities contained in the work of Jane Jacobs. Particularly in reference to the relationship between environment built of cities and urban vitality, with emphasis on the political and economic aspects linked to the environment built. For this task a dialogue with the work of Jane Jacobs is established from two books: Death and Life of Great Cities whose first edition dates from 1961, The Economy of Cities published in 1969. Two other books appear in the text as elements of corroboration of some contextualization about the authoress: The Systems of Survival of 1992 and its last book, Dark Age Ahead of 2005. It intends to analyze possible contributions and perspectives present in the work of the authoress on the active role of the constructed means of the cities in the conformation of alternatives and ways of fighting for a life with a minimum of material dignity.